An Efficient and Eco‐Friendly Synthesis of Protoberberine and 13‐Me Protoberberine Alkaloids via Electrochemical Acceptorless Dehydrogenation. Issue 7 (27th February 2023) - Li, Weijian; Huang, Shiqi; Jiang, Meifen; Chen, Yu; Yang, Zhi; Tang, Pei; Chen, Fener
Abstract: A practicable and environmentally benign process for the synthesis of protoberberine (PB) and 13‐methylprotoberberine (13‐MePB) alkaloids is reported. In contrast to previous dehydrogenation of saturated C ring utilizing a stoichiometric oxidant, the electrocatalytic approach through I2 ‐mediated electrochemical acceptorless dehydrogenation (ECAD) can eco‐efficiently construct aromatized C ring of PBs and 13‐MePBs in last‐stage. This new method to the aromatization of tetracyclic framework has been applied to divergent syntheses of ten PBs and eight 13‐MePBs in high yields. Importantly, this I2 ‐ECAD protocol can be conducted on a gram scale and applied in a continuous‐flow microreactor successfully. Given such practicability and efficiency, the developed synthetic strategy meets many salient features of green chemistry, and would be greatly beneficial to the synthesis of important isoquinoline fine chemicals and relevant natural products. Abstract : Natural product electrosynthesis : An eco‐friendly protocol for the synthesis of protoberberine and 13‐Me protoberberine alkaloids relies on electrochemical acceptorless dehydrogenation at the last stage, using 10 mol% I2 as redox mediator at room temperature under mild reaction conditions.